Fragmentation Patterns of Radiosensitizers Metronidazole and Nimorazole upon Valence Ionization - Itälä Eero; Niskanen Johannes; Pihlava Lassi; Kukk Edwin (AMER CHEMICAL SOC, 2022)
We study gas-phase photodissociation of radiosensitizer molecules nimorazole and metronidazole with the focus on the yield of the oxygen mimics nitrogen oxides and nitrous acid. Regardless of photon energy, we find the nimorazole cation to split the intramolecular bridge with little NO2 or NO production, which makes the molecule a precursor of dehydrogenated methylnitroimidazole. Metronidazole cation, on the contrary, has numerous fragmentation pathways with strong energy dependence. Most notably, ejection of NOOH and NO2 takes place within 4 eV from the valence ionization energy. Whereas the NO2 ejection is followed by further fragmentation steps when energy so allows, we find emission of NOOH takes place in microsecond time-scales and as a slow process that is relevant only when no other competing reaction is feasible. These primary dissociation characteristics of the molecules are understood by applying the long-known principle of rapid internal conversion of the initial electronic excitation energy and by studying the energy minima and the saddle points on the potential energy surface of the electronic ground state of the molecular cation.